HUMAN SECURITY AND MIGRATION: HUMAN RIGHT VIOLATIONS AND CHALLENGES OF ETHIOPIAN MIGRANTS IN THE MIDDLE EAST - Seada Hassen Endris (Journal of International Trade, Logistics and Law, 2019)
Migration is currently considered as one of the foremost issues that the world is dealing with. According to UNDESA 2017 report there exist 258 million international migrants globally in the year 2017 (United Nations, 2017). When it comes to being a migrant destination, the Middle East region is one of the major spots especially for migrant workers. The region is also a popular destination for Ethiopian migrants. It is estimated that 44% of Ethiopian migrants globally is found in the Middle East region (Kuschminder , et al., 2013). Ethiopians migrate to this region because of breach and omission of their social, economic and political rights in their home country. Moreover, they face various types and degree of human right abuses and violations in their way and destination to the Middle East. This article looks deep and analyzes the concept of human security and its implication in migration studies. Moreover, it emphasizes on challenges and human right violations that Ethiopian migrants face in their home country, in their way and destination in the Middle East that jeopardizes their human security. The article is written by reviewing and analyzing various academic works on the area and surveys and reports of governmental and nongovernmental organizations.